The Role of Veterinarians in Managing Community Cats: A Contextualized, Comprehensive Approach for Biodiversity, Public Health, and Animal Welfare - Octavio P. Luzardo; José Enrique Zaldívar-Laguía; Manuel Zumbado; María del Mar Travieso-Aja (Animals, 2023)
Homeless cats are a major problem in Europe, with hundreds of thousands abandoned every year. While many die, others can adapt to a lifestyle of roaming freely and establish community cat populations that tend to cluster together in groups. These groups of cats are typically found in urban areas that offer food and shelter to the cats. Animal welfare organizations often care for these cats, providing them with food, shelter, and medical attention. Despite this, conflicts can arise due to the presence of free-roaming cats, with some individuals advocating for drastic measures such as trapping and killing the cats to reduce their populations. However, it is essential to note that such methods are frequently illegal, inhumane, and ultimately ineffective in most situations. A thorough assessment of the impact of cats on a particular natural area requires a comprehensive cat census, a detailed study of the species being preyed upon, and an investigation into the prevalence of zoonotic or epizootic diseases. Moreover, veterinary experts assert that the public health risks associated with cats are often overstated. This article aims to provide a nuanced perspective on the impact of cats on biodiversity in natural areas, while also discussing their role in transmitting the main zoonotic diseases identified in European countries in recent years, with a particular focus on Spain. Effective cat control programs should focus on non-lethal methods such as trap–neuter–return (TNR) and adoption. TNR has proven to be the most effective and humane method of controlling the free-roaming cat population, but its effectiveness is influenced by several factors, including adoption programs and public education on responsible pet ownership. According to Spanish veterinarians, sustainable and science-based solutions such as TNR programs are the best way to achieve population control of free-roaming cats. The veterinary profession should raise awareness regarding sterilization, vaccination, and identification of cats and the consequences of abandonment. They oppose lethal control and removal of cats from the environment, which are ineffective and unethical methods. To promote animal welfare, veterinary professionals must collaborate with public administrations to implement long-term, sustainable solutions to the problem of cat overpopulation. Greater social awareness regarding the importance of sterilization and identification to prevent abandonment and reduce the number of free-roaming cats is also needed. Despite the challenges presented by homeless cat populations in Spain and the rest of Europe, there are many reasons for optimism. Animal welfare organizations and veterinary professionals are actively collaborating to develop humane and effective solutions to manage community cats, including programs such as TNR and adoption. Furthermore, these initiatives are gaining momentum and support from emerging laws and regulations, such as the recent Spanish animal welfare law. Through these efforts, we can reduce the number of free-roaming cats and improve their quality of life.